ORGANIC FARMING PRACTICES FOR ENHANCING SOIL FERTILITY AND CROP PRODUCTIVITY - SITA KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
There is a significant amount of manure resource potential in India. Farmers in Kerala, the southernmost state of India, employ organic manures such as farm yard manure and chicken waste the most frequently. Kerala is India's southernmost state. The cultivation of vegetables, in particular, benefits greatly from the addition of poultry manure to their soil. The breakdown of organic waste into its component parts by earthworms results in the production of vermicompost, which is rich in various nutrients, hormones, and enzymes and has a stimulatory influence on the development of plants. Because it is such a rich source of protein, cowpea is one of the most significant vegetable crops that can be found in Kerala's diverse agricultural landscape. The experimental land had a flat terrain and a consistent textured composition over its entirety. It was extremely fruitful. It was connected to the primary irrigation channel, which was linked to the farm tube well to ensure that the irrigation process was quick, routine, and on schedule. This endeavour was undertaken in order to find out how these variations may be measured. At the time of harvesting, growth characteristics as well as yield characteristics were observed. In addition, the biological, chemical, and physical features, as well as the enzymatic activities and nutritional contents of the soil and plants, were investigated. During the course of the inquiry, the data that were gathered were subjected to the conventional method of statistical analysis so that appropriate conclusions could be drawn.